Optimal Search for Product Information - Branco, Fernando; Sun, Monic; Villas-Boas, J. Miguel (Management Science, 2012)
Consumers often need to search for product information before making purchase decisions. We consider a tractable (continuous-time) model of gradual learning, in which consumers incur search costs to learn further product information, and update their expected utility of the product at each search occasion. We characterize the optimal stopping rules for either purchase, or no purchase, as a function of search costs and of the importance/informativeness of each attribute. This paper also characterizes how the likelihood of purchase changes with the ex ante expected utility, search costs, and the importance/informativeness of each attribute. We discuss optimal pricing, the impact of consumer search on profits and social welfare, and how the seller chooses its price to strategically affect the extent of the consumers' search behavior. We show that lower search costs can hurt the consumer because the seller may then choose to charge higher prices. Discounting creates asymmetry in the purchase and no-purchase search thresholds, and may lead to lower prices if search occurs in equilibrium, or higher prices if there is no search in equilibrium. This paper also considers searching for signals of the value of the product, heterogeneous importance of attributes, endogenous intensity of search, and social learning. This paper was accepted by Pradeep Chintagunta, marketing.